2010
DOI: 10.1111/j.1440-1754.2010.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxine‐dependent epilepsy: An under‐recognised cause of intractable seizures

Abstract: Pyridoxine-dependent epilepsy (PDE) is a rare autosomal recessive disorder causing intractable seizures in neonates and infants. PDE patients are typically resistant to anti-epileptic treatment but respond to the administration of pyridoxine. Different seizure types have been reported in PDE, and episodes of status epilepticus are common. Electroencephalographic or neuroimaging abnormalities are not pathognomonic for this disorder. Intellectual disability is frequent at the follow-up. Recently, elevated urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…In regards, several studies have suggested a neuroprotective effect of LEV in both epileptic and nonepileptic disorders. [161718192021] LEV has been demonstrated to increase the expression of gamma glutamate transporters (GLTs) excitatory amino acid transporter 1/glutamate–aspartate transporter (EAAT1/GLAST) and EAAT2/GLT1, which mechanism has been proposed one of the most important effects of LEV in neuroprotection. [1516] This hypothesis fits well with those changes described in brains after traumatic insults, consisting in increased concentration of glutamate in the extracellular areas, with secondary enhanced activation of N-methyl-D-aspartate receptors and alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors on neurons and culminating in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards, several studies have suggested a neuroprotective effect of LEV in both epileptic and nonepileptic disorders. [161718192021] LEV has been demonstrated to increase the expression of gamma glutamate transporters (GLTs) excitatory amino acid transporter 1/glutamate–aspartate transporter (EAAT1/GLAST) and EAAT2/GLT1, which mechanism has been proposed one of the most important effects of LEV in neuroprotection. [1516] This hypothesis fits well with those changes described in brains after traumatic insults, consisting in increased concentration of glutamate in the extracellular areas, with secondary enhanced activation of N-methyl-D-aspartate receptors and alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors on neurons and culminating in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…[1516] This hypothesis fits well with those changes described in brains after traumatic insults, consisting in increased concentration of glutamate in the extracellular areas, with secondary enhanced activation of N-methyl-D-aspartate receptors and alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors on neurons and culminating in neurodegeneration. [161718192021] In this context, LEV has also been demonstrated to decrease the expression of pro-oxidant protein-inducible nitric oxide synthase and increase the expression of the antioxidant protein cysteine/glutamate exchanger in the hippocampus,[20] diminishing those damages caused by seizure-induced oxidative stress. [22]…”
Section: Discussionmentioning
confidence: 99%
“…Often times, neurologists will administer pyridoxal-5 0 -phosphate to intractably seizing neonates if they fail the pyridoxine challenge so as to not miss this rare disorder. The best diagnostic test, however, is measuring pyridoxal-5 0 -phosphate in the CSF [9].…”
Section: Disorders With Available Treatmentmentioning
confidence: 99%
“…For patients who have responded to therapy testing can be performed for mutations in known genes. 117 Other vitamin response epilepsies will typically present during infancy, but late onset PNPO deficiency responding only to PLP as well as late onset biotinidase deficiency responding to biotin have both been described. 118,119 Thus, a trial of PLP or biotin could be considered in refractory SE.…”
Section: Refractory Status Epilepticusmentioning
confidence: 99%